If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2y) = 1 + -3(x + -6y + 43) (x * 5 + 2y * 5) = 1 + -3(x + -6y + 43) (5x + 10y) = 1 + -3(x + -6y + 43) Reorder the terms: 5x + 10y = 1 + -3(43 + x + -6y) 5x + 10y = 1 + (43 * -3 + x * -3 + -6y * -3) 5x + 10y = 1 + (-129 + -3x + 18y) Combine like terms: 1 + -129 = -128 5x + 10y = -128 + -3x + 18y Solving 5x + 10y = -128 + -3x + 18y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 5x + 3x + 10y = -128 + -3x + 3x + 18y Combine like terms: 5x + 3x = 8x 8x + 10y = -128 + -3x + 3x + 18y Combine like terms: -3x + 3x = 0 8x + 10y = -128 + 0 + 18y 8x + 10y = -128 + 18y Add '-10y' to each side of the equation. 8x + 10y + -10y = -128 + 18y + -10y Combine like terms: 10y + -10y = 0 8x + 0 = -128 + 18y + -10y 8x = -128 + 18y + -10y Combine like terms: 18y + -10y = 8y 8x = -128 + 8y Divide each side by '8'. x = -16 + y Simplifying x = -16 + y
| 16.2=R+1.75*(11-R) | | a=7/tan40.5 | | -5(-1+6)=x | | tan40.5=7/a | | r+5/6=2/3 | | -(3/5)n-(7/10)n | | (3x-4)(x+5y)= | | 2x+10y=-30 | | 4x+2=x+3x+5-3 | | 4e^4x=220 | | x/2.4=4.2 | | 22x=323y | | (9x^9/y)^-3 | | x/2-1/2=5/6 | | 30/x=6/2 | | 3d^2(d-7)=0 | | 12.8=w/4 | | 2a^2+5a+1=0 | | 5y=6.25 | | x=6.875+0.04166667(43.421) | | X/3=3.84 | | 3x-7x-28=-4x+6 | | 285-x=25 | | 5=2/5-8/z | | y=41.25+0.25(6.875+0.041666667y) | | -u+146=220 | | 168=82-u | | (-x+26)(x^2-10x+16)=28(x^2-10x+16) | | -7x+8*(-2x+5)= | | 8x+12=10x+24 | | 5u^2-3=14u | | (2y^3*9-y+16)-(5y^3+3y-3)= |